POP Trial: Similar Functional Results in Each Treatment Method for Midshaft Clavicle Fractures - Hoyle, Brian (MD Conference Express, 2014)
Frans-Jasper G. Wijdicks, MD, PhD, Diakonessenhuis, Utrecht, The Netherlands, reported the results of the randomized controlled Surgical Treatment of Midshaft Clavicular Fractures With Dislocation trial [POP; NTR2438], which compared the short- and mid-term outcomes of plate fixation and intramedullary (IM) nailing. Midshaft fractures were the focus because 80% of all clavicle fractures occur in the midshaft region, and half of the fractures involve dislocation.